2016
DOI: 10.1111/jfd.12579
|View full text |Cite
|
Sign up to set email alerts
|

Search and analysis of genes involved in antibiotic resistance in Chilean strains of Piscirickettsia salmonis

Abstract: Piscirickettsia salmonis is the pathogen causing Piscirickettsiosis. For treatment, the industry mainly uses oxytetracycline and florfenicol, so it is essential to understand the degree of susceptibility of this pathogen to these drugs. But this is still unknown for a large number of P. salmonis strains, as are the molecular mechanisms responsible for greater or lesser susceptibility. However, genes that confer resistance to these antimicrobials have been reported and characterized for this and other bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
(56 reference statements)
1
22
0
Order By: Relevance
“…; Cartes et al . ). The MIC was determined for the type strain LF‐89, which showed values ranging from 0.08 to 0.25 μg/mL for oxytetracycline and florfenicol.…”
Section: Piscirickettsia Salmonismentioning
confidence: 97%
“…; Cartes et al . ). The MIC was determined for the type strain LF‐89, which showed values ranging from 0.08 to 0.25 μg/mL for oxytetracycline and florfenicol.…”
Section: Piscirickettsia Salmonismentioning
confidence: 97%
“…This evidence is based on what has been seen with respect to the expression of the ompF gene, which encodes for a porin. Previous studies have shown the greater EtBr accumulation capacity of isolates when compared to other field strains of P. salmonis (Cartes et al, ; Sandoval et al, ). It must be noted that strain Psal‐010 accumulated the lowest internal amount of EtBr, which correlates with the observations in the MIC assays.…”
Section: Discussionmentioning
confidence: 93%
“…The expression kinetics for each of the strains under study was evaluated at a single concentration of the antibiotic and at different times, with the purpose to determine the relationship between the SNPs present in the resistance genes and their expression levels. Previously, we reported the results of analyses performed with oxytetracycline and florfenicol at two different concentrations, which were regarded as non‐lethal to the bacterium (Cartes et al, ). In this regard, two oxytetracycline resistance genes, showing a high number of polymorphisms among the type and field strains, were analysed (Table ), and also a gene encoding for a porin (OmpF), which also had SNPs among strains, as evidenced when comparing their tertiary structures (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, there is evidence that bacteria from sites used by aquaculture are more resistant to antibiotics and they have been able to transfer the resistance to bacteria in non-contaminated areas (Kerry et al 1996;Winsby et al 1996;Miranda & Zemelman 2002;Chelossi et al 2003;Shakouri 2003). Several studies in Chile have also reported that P. salmonis has developed antimicrobial resistance to antibiotics (Shah et al 2014;Tomova et al 2015Tomova et al , 2018Cartes et al 2017;Lozano et al 2018). Tomova et al (2015) studied acquired antimicrobial resistance genes (ARG) in the presence of tetracycline, florfenicol and quinolones in antimicrobial-resistant bacteria (ARB) from the water column and sediments of aquaculture-influenced sites.…”
Section: Antibioticsmentioning
confidence: 99%